2021
DOI: 10.1108/jaar-04-2021-0097
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reporting quality and cost of debt financing

Abstract: PurposeIn recent years, policymakers have increasingly pushed firms to disclose non-financial information. In Europe, integrated reporting (IR) is an increasingly adopted tool to fully comply with the requirements of the Directive 2014/95/EU. This study aims to examine the financial benefits of IR quality and specifically the effect on the cost of debt.Design/methodology/approachA manual content analysis is performed to measure the quality of the information contained in integrated reports. A panel regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 80 publications
4
33
0
8
Order By: Relevance
“…Only few studies to date have considered IRQ in a voluntary setting. Raimo et al (2021) report a slightly negative effect of IRQ on the cost of debt for European firms. By focussing on debt capital markets and borrowing conditions of voluntary IR adopters, however, they do not analyze the information environment particularly relevant for equity investors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few studies to date have considered IRQ in a voluntary setting. Raimo et al (2021) report a slightly negative effect of IRQ on the cost of debt for European firms. By focussing on debt capital markets and borrowing conditions of voluntary IR adopters, however, they do not analyze the information environment particularly relevant for equity investors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Indeed, it might be that only high‐quality integrated reports provide an effective mechanism in voluntary settings. Latest research results indicate that IRQ is the more meaningful variable (Raimo et al, 2021). Hence, the current study examines the informational effects of IRQ in a setting of voluntary adoption.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…By strengthening these links, IRQ can help companies make more sustainable decisions and enable investors and other stakeholders to understand an organization’s true performance. Several studies have highlighted the benefits of IRQ, Muttakin et al (2020) and Raimo et al (2021) reported that IRQ is beneficial for management because it allows a better understanding and a clear articulation of the relationships between financial and nonfinancial performance. As a result, IRQ also enables better risk management and better engagement of current and potential employees and other stakeholders.…”
Section: Formulation Of Hypothesesmentioning
confidence: 99%
“…These disclosures provide a lot of information related to pollution, gender policies, governance regime and environment friendly products. As a matter of fact, non-financial disclosure is of concern for various stakeholders, such as customers, workers and government (Raimo et al, 2019; Vitolla et al, 2019a; 2019b). Non-financial disclosure can remove the problem of information asymmetry between the management and investors (Vitolla & Raimo, 2018), which eventually will reduce cost of capital of the firm.…”
Section: Introductionmentioning
confidence: 99%